Особливостi перколяцiйного переходу в системах на основi олiгоглiколiв та вуглецевих нанотрубок - Klepko, V. V.; Lysenkov, E. A. (Publishing house "Academperiodika", 2019)
The results of researches on the electric conductivity in the percolation transition region of the oligoglycol/nanotubes systems are reported. It is shown that the conductivity can be described in the framework of the critical percolation theory. The critical parameters of percolation transition are found to change, by depending on various factors, and to differ from the predictions of the statistical percolation theory. A relationship between the critical conductivity indices and the fractal dimensionality of a conducting cluster is found. It is demonstrated that the application of a scaling function allows the concentration dependences of conductivity to be described with the help of a unique universal function.